New Insight into Post-seismic Landslide Evolution Processes in the Tropics - Tanyaş, Hakan; Kirschbaum, Dalia; Görüm, Tolga; van Westen, Cees J.; Lombardo, Luigi (Frontiers in Earth Science, 2021)
Earthquakes do not only trigger landslides in co-seismic phases but also elevate post-seismic landslide susceptibility either by causing a strength reduction in hillslope materials or by producing co-seismic landslide deposits, which are prone to further remobilization under the external forces generated by subsequent rainfall events. However, we still have limited observations regarding the post-seismic landslide processes. And, the examined cases are rarely representative of tropical conditions where the precipitation regime is strong and persistent. Therefore, in this study, we introduce three new sets of multi-temporal landslide inventories associated with subsets of the areas affected by (1) 2016 Reuleuet (Indonesia, Mw=6.5), (2) 2018 Porgera (Papua New Guinea, Mw=7.5) and (3) 2012 Sulawesi (Indonesia, Mw=6.3), 2017 Kasiguncu (Indonesia, Mw=6.6) and 2018 Palu (Indonesia, Mw=7.5) earthquakes. Overall, our findings show that that the landslide susceptibility level associated with the occurrences of new landslides return to pre-seismic conditions in less than a year in the study areas under consideration. We stress that these observations might not be representative of the entire area affected by these earthquakes but the areal boundaries of our study areas.